The Influence of Feedback in Different Way of Learning and the Relationship with Students’ Vocabulary Acquisition: Issues in Assessment - Irham Mifta (STKIP PGRI SIDOARJO, 2021)
Abstract This paper has three components. They are feedback, the way of learning, and vocabulary acquisition. This research was based on the learning situation that teachers and students have to conduct online learning because of the pandemic Covid 19. This paper elaborates the three components mentioned before. In the process of assessment, feedback is the important part. When students learning at school, teachers will give feedback directly. The way of giving feedback in language learning will influence students’ vocabulary acquisition. But, in different way of learning, teachers cannot give feedback directly as in the classroom. This situation gives different influence in students’ vocabulary acquisition. Then teachers do the alternative assessment in the process of online learning. Keywords: Feedback, Vocabulary Acquisition, Assessment